1994
DOI: 10.1073/pnas.91.15.7076
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a melanosomal matrix protein encoded by the murine si (silver) locus using "organelle scanning".

Abstract: To Identify a broad sperm of melanosomal proteins, antisera were raised In rabbits against melanosomal protein fractions separated on the basi oftheir soubilit in the onic detergent Triton X-114. Antisera METHODS Subceflular Fractionation and Prparation of Antisera. Melanosomes were purified as described (7) from B16 cells grown as tumors subcutaneously in C57BL/6J mice. Stage III-IV melanosomes made up >90%6 ofthe organelles in the purified fraction as assessed by electron microscopy (7). To further fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 24 publications
1
49
0
Order By: Relevance
“…The two antibodies that recognize GP100 (i.e., ␣PEP13 and HMB45) show radically different reactivity patterns. The epitope for HMB45 is on an interior motif of the protein whereas ␣PEP13 recognizes the carboxyl terminus (5,6,33). Previous metabolic labeling and pulse-chase analysis combined with sucrose density gradient subcellular fractionation previously showed that processing of GP100 is very quick compared with the TYRPs, and that it is not processed through the trans-Golgi network, but follows a route distinct from the TYRPs to be sorted to melanosomes (5).…”
Section: Distribution Of Melanosomal Proteins After Purification By Ffementioning
confidence: 99%
See 1 more Smart Citation
“…The two antibodies that recognize GP100 (i.e., ␣PEP13 and HMB45) show radically different reactivity patterns. The epitope for HMB45 is on an interior motif of the protein whereas ␣PEP13 recognizes the carboxyl terminus (5,6,33). Previous metabolic labeling and pulse-chase analysis combined with sucrose density gradient subcellular fractionation previously showed that processing of GP100 is very quick compared with the TYRPs, and that it is not processed through the trans-Golgi network, but follows a route distinct from the TYRPs to be sorted to melanosomes (5).…”
Section: Distribution Of Melanosomal Proteins After Purification By Ffementioning
confidence: 99%
“…These include tyrosinase (TYR), the tyrosinase-related proteins-1 and -2 (TYRP1͞TRP1 and DCT͞TRP2, respectively; refs. 1-3), GP100͞Pmel17͞silver (4)(5)(6), and Pink (7)(8)(9). In addition, another protein, termed MART1 (melanoma antigen recognized by T lymphocytes), has been cloned that localizes in melanosomes (10,11), but its function there remains unclear.…”
mentioning
confidence: 99%
“…For immunofluoresence analysis, ␣Pep7 was further affinity purified using the Pep7 peptide linked to an Affigel15 column (Bio-Rad, Hercules, CA). The polyclonal antibody ␣Pep13 was generated against the C terminus of the mouse silver protein (Zhou et al, 1994). The following antibodies were also used: GRP78/bip, syntaxin 6, and Vti1b (Transduction Laboratories, Lexington, KY); ribophorin (obtained from Dr. G. Kreibich, New York University Medical Center, New York, NY); anti-V5 antibody (Invitrogen, San Diego, CA); Mel-5 (Signet, Dedham, MA), and Calnexin (StressGen, Victoria, British Columbia, Canada).…”
Section: Antibodiesmentioning
confidence: 99%
“…Tyr distribution was biphasic with a predominant peak in the melanosome fractions 1-3 and a minor peak in the Golgi/ER fractions. To determine whether p is located in premelanosomes, we used ␣Pep13 against the silver protein as a premelanosome marker (Zhou et al, 1994;Raposo et al, 2001). The premelanosomes were found between fractions 9 and 11, in a single peak and one fraction lighter than p. Thus, most p is not present in premelanosomes.…”
Section: The Majority Of P Is Located In the Ermentioning
confidence: 99%
“…Although this gene is known to have a central role in pigmentation, the precise function of SILV remains controversial (24). Multiple studies have provided data to suggest that SILV is involved in the biogenesis of premelanosomes (25)(26)(27). Significant expression of the gene is almost exclusive to the skin and eye, providing further evidence to support a role in pigmentation (24).…”
mentioning
confidence: 99%